INVESTIGATING PARENTAL INVOLVEMENT ON STUDENTS’ ENGLISH ACHIEVEMENT - Kunah Kunah; Supriyani Supriyani (STIBA IEC JAKARTA, 2022)
This study is aimed to investigate parental involvement on students’ English achievement. And this study is also aimed to investigate English achievement in Students SMP Negeri 1 Lohbener, to know the impacts parental involvement, furthermore how far and perception parental involvement on students’ English achievements. This research used a qualitative research paradigm: a case study approach. This case study is conducted to three students who have different scoring and would like to be investigated. Those students are three students who identified as the high, middle, and low achievement in the English classroom. In three students are affected by parents or not in their process achievements. To investigate them, this study employed four instruments; documentation, questionnaire, observation, and informal interviews. The finding from questionnaire Percentage Levels of Each Students’ Achievement. The finding which is gained from questionnaire revealed that all three participants; Putri Soleha (A), Catur Piyanti (B), and Sunanto (C). In sequentially, their involvement with parents is 70%, 42%, and 27,5%. Putri has a high of parental involvement, then Catur has a middle of parental involvement, and finally Sunanto has a lack of parental involvement. And reality is Putri has higher achievement than Catur and Sunanto.